Lithium chloride-imidazolium chloride melts for the coupling reactions of propylene oxide and CO2 - Nguyen, Ly Vinh; Lee, Bora; Nguyen, Dinh Quan; Kang, Min-Jung; Lee, Hyunjoo; Ryu, Seol; Kim, Hoon Sik; Lee, Je Seung (WILEY-V C H VERLAG GMBH, 2008)
A series of lithium chloride-imidazolium chloride (LiCl-[imidazolium]Cl) melts were prepared and their catalytic activities were evaluated for the coupling reactions of propylene oxide and CO2. At the constant mole of LiCl, the catalytic activities of LiCl-[imidazolium]Cl melts increased with increasing molar ratio of [imidazolium]Cl/LiCl up to 2, but thereafter decreased rapidly. The variation of alkyl groups on the imidazolium ring showed a negligible effect on the catalytic activity, but the number of alkyl groups present on the imidazolium cation exerts a pronounced effect. Catalysis and electrospray ionization tandem mass spectral analysis results of LiCl-[imidazolium]Cl melts imply that the activity of the melt is strongly related to the amount of LiCl2- generated from the melt.
Keywords: TEMPERATURE IONIC LIQUIDS; CYCLIC CARBONATES; ETHYLENE-OXIDE; EPOXIDES; DIOXIDE; CATALYST; HALIDE; SYSTEM